Combined application of macro and micro nutrients and Rhizobium inoculation to nodulation and yield response of chickpea (Cicer Arietinum L.) at Halaba Woreda, Southern Ethiopia - Tilahun, Meklit; Worku, Walelign; Mohammed, Semira; Tamiru, Tatek; Wolde, Girma; Nahusenay, Gashaw (Journal of Phytology, 2023)
The effects of combining the application of recently introduced blended fertilizer with Rhizobium inoculation on chickpea nodulation and productivity are not being studied in Halaba special woreda. Hence, the application of blended fertilizer and rhizobium inoculation for chickpea production under rain-fed conditions at Halaba Special District, Southern Ethiopia is crucial. Factorial combination of eight fertilizers (Control, NP, NPS, NPSB, NPSB+K, NPS+Zn, NPSB+Zn and NPSB+K+Zn) and inoculation and without inoculation of rhizobium biofertilizer was used as an experimental factor laid out in a randomized complete block design with three replications. Fertilizer application significantly influenced crop phenology, nodulation, growth parameters, yield and yield components, except number of seeds pod-1 and harvest index. Maximum days to 50% flowering (48.33) and 95% physiological maturity (112.3) were obtained on NPSB+K and without fertilizer treatment respectively. The Highest number of nodules (23.25), nodules dry weight (0.13 g), number of branches plant-1 (17.64) and plant height (43.34 cm) were recorded on NPSB, NPSB+K+Zn, NPSB+Zn and NPS+Zn respectively. Similarly, the higher number of pods plant-1(61.6), and hundred seed weight (28.0 g) were observed for blended fertilizer treatments of NPSB+K and NPS+Zn respectively. Maximum grain yield (1.85 ton ha-1) was obtained for blended fertilizer of NPSB+K application with an increment 57.9% over control treatment. Rhizobium inoculation increased the number of nodules plant-1 (23.29), nodules dry weight (0.11 g), number of branches plant-1 (17.70), number of pods plant-1 (59), number of seeds pod-1 (1.17) and hundred seed weight (27.7 g). Maximum grain yield (1.84 ton ha-1) was recorded on rhizobium inoculated and it increased chickpea grain yield by 33.3% over uninoculated. Regarding the economic feasibility of fertilizers greater net benefits with acceptable MRR 1802, 866 and 257 were recorded for blended fertilizers of NPS, NPS+Zn and NPSB, respectively. Given the fact that the three fertilizers had statistically similar grain yields, the blended fertilizer NPS is a better choice among the three alternatives. Similarly, a higher net benefit with acceptable MRR (4189%) was recorded for Rhizobium inoculation. Therefore, blended fertilizer; NPS and Rhizobium inoculation were found to be relevant and recommended for chickpea production in the study area.